The need to improve fertility awareness. (June 2017) - Harper, Joyce; Boivin, Jacky; O'Neill, Helen C.; Brian, Kate; Dhingra, Jennifer; Dugdale, Grace; Edwards, Genevieve; Emmerson, Lucy; Grace, Bola; Hadley, Alison; Hamzic, Laura; Heathcote, Jenny; et al.
Abstract: Women and men globally are delaying the birth of their first child. In the UK, the average age of first conception in women is 29 years. Women experience age-related fertility decline so it is important that men and women are well-informed about this, and other aspects of fertility. A group of UK stakeholders have established the Fertility Education Initiative to develop tools and information for children, adults, teachers, parents and healthcare professionals dedicated to improving knowledge of fertility and reproductive health.